(untitled) (Philologia, 2021)
This paper begins with a brief general outline of Evelyn Waugh’s life and work, and proceeds to a survey of the critical reception of Waugh’s novels in Serbo-Croat journals, periodicals and literary studies, which are presented chronologically, from the first mention of his work until the end of the period under consideration, in 1992, when former Yugoslavia fell apart. Research shows that, although this writer has been regarded by many British critics as the leading satirical novelist of his day, during his lifetime, translations of his novels were not available to a Yugoslav readership to the extent which his international fame would deserve. This especially holds in the case of Waugh’s early novels, which reflect the modernist crisis by depicting the rootlessness, alienation and disorientation of British youth in the aftermath of World War I, and even more in the case of his war trilogy, assessed by critics in his own country as the best English novel about World War II. However, besides a few short informative critical commentaries, several comparatively complete accounts of Waugh’s life and work have been published, two of them written by Vida Marković and one by Svetozar M. Ignjačević.